Rainfall as a risk factor for flooding in the Hulene B neighbourhood in Maputo City - Zandamela , Osvaldo Francisco; Cossa, Freitas Fenias (Seven Editora, 2024)
This article aims to analyze the risk of flooding resulting from rainfall in the neighborhood of Hulene "B" in Maputo City. The analytical perspective focuses on the social scope of the risk, taking into account its impact on the population residing in that area. The study will privilege the mixed method with a focus on bibliographic research based on literary works that address the same theme. During the study, it was found that the forecast for the occurrence of precipitation advanced by INAM for the period from October 2022 to March 2023 is for the occurrence of rainfall with a trend from normal to above normal. Thus putting a good part of the "Hulene B" neighborhood at risk of flooding. DOI:https://doi.org/10.56238/sevened2024.010-009